Pengawasan Dana Kampung Oleh Badan Permusyawaratan Desa - Serano Vincen (Musamus Journal of Public Administration, 2020)
The purpose of this study was to determine the supervision of village funds by the village consultative body (BPD) in Kampung Poo, Jagebob District, Merauke Regency. The research method used is a qualitative method, descriptive qualitative research type. The research was conducted through observation and in-depth interviews. After that the data obtained is collected to be described and analyzed to draw a conclusion. The results showed that the supervision of the Village Funds by the Village Consultative Body (BPD) in Kampung Poo has not been going well, especially at the pre-distribution stage and the distribution and use of Village funds, only the third stage has been carried out well, but the Pre-Distribution Stage of Village Funds is still not carried out well, especially in the Aspect of Appropriateness of the Village Fund Planning Arrangement Procedure because the village head did not make a decision letter regarding the Village Fund Implementing Technical Officer (PTPD) but only made direct appointments to the village secretary and head of financial affairs, and the distribution and use stage, namely in the financial aspect and use, where the People's Consultative Body (BPD), which is the representative of the community at large to oversee the Village Fund Budget, does not get the opportunity to consult to determine priority programs funded by village funds so that supervision of village funds is still not very effective.